Implant for autologous soft tissue reconstruction using an adipose-derived stem cell-colonized alginate scaffold. Issue 1 (January 2018) - Hirsch, Tobias; Laemmle, Christine; Behr, Bjoern; Lehnhardt, Marcus; Jacobsen, Frank; Hoefer, Dirk; Kueckelhaus, Maximilian
Summary: Background: Adipose-derived stem cells represent an interesting option for soft tissue replacement as they are easy to procure and can generate their own blood supply through the production of angiogenic factors. We seeded adipose-derived stem cells on a bioresorbable, biocompatible polymer alginate scaffold to generate autologous soft tissue constructs for repair. Materials and methods: We built and optimized an alginate scaffold and tested its biocompatibility using the MTT assay and its hydration capacity. We then isolated, characterized, and differentiated murine, porcine, and human adipose-derived stem cells. We characterized their angiogenic potential in vitro by VEGF ELISA and HUVEC tube formation assay in traditional cell culture substrate and in the actual three-dimensional scaffold. We assessed the angiogenic potential of adipose-derived stem cell-colonized scaffolds in ovo by chorion allantois membrane angiogenesis assay. Results: Adipose-derived stem cells differentiated into adipocytes within the alginate scaffolds and demonstrated angiogenic activity. VEGF secretion by adipose-derived stem cells decreased significantly over the 21-day course of adipocyte differentiation in traditional cell culture substrate, but not in scaffolds. Adipose-derived stem cells differentiated for 21 days in scaffolds led to the longest HUVEC tube formation. Scaffolds colonized with adipose-derived stem cells resulted in significantly improved vascularization in ovo . Conclusions: We demonstrate the feasibility of implant production based on adipose-derived stem cell-colonized alginate scaffolds. The implants demonstrate biocompatibility and promote angiogenesis in vitro and in ovo . Therefore, they provide a combination of essential properties for an implant intended for soft tissue replacement.